Physical child abuse and self-reported health concerns: A case-control study including police-reported cases and unreported controls - Daniella Justesen; Carl Johan Wingren; Liselott Slot; Maria Balsløv; Andrea Lykke Thanning; Jytte Banner (PLoS ONE, 2025)
Background Child abuse continues to pose a significant threat to children’s health. The repercussions of abuse are profound, impacting the child’s physical, social, and emotional well-being, with potential long-term effects that may extend into adulthood. To assist in identifying health concerns in children associated with exposure to physical abuse, a health questionnaire was developed to be used in the setting of a forensic examination. Objective This study examines whether children suspected of being exposed to physical violence report more health-related concerns compared to unexposed controls. Participants and setting The case group consists of children suspected of being exposed to physical violence, with reports to the Copenhagen police. Cases were examined from April 1, 2020, to December 31, 2023, at the Child Advocacy Centre (CAC) in Copenhagen, totaling 374 examinations. A control group of children aged 4–14 years with no suspicion of abuse was established through recruitment via social media platforms (Facebook, LinkedIn), posters, and word of mouth. Controls were examined from November 1, 2023, to September 30, 2024, totaling 122 examinations. Methods Children underwent a standardized forensic examination, which included a health interview reviewing health behaviors (e.g., diet, toothbrushing, and sleep patterns) and well-being (liking school/preschool, having friends, and trusted adults). Results Overall, cases reported significantly more concerns than controls on several assessed items. With multivariate logistic regression, adjusted for all significant covariates and stratified by age, two concerns remained significant. Cases aged 8–14 years, had significantly higher odds of brushing their teeth once daily or less (OR: 3.85; CI: 1.47–10.12) and reported low enjoyment of school (OR: 3.74; CI: 1.03–13.53). Conclusions Health interviews may support the identification of children at risk. However, the statistical power was limited, and the findings require validation in larger populations.